Duodenal atresia in 17q12 microdeletion including HNF1B: A new associated malformation in this syndrome. Issue 12 (24th September 2014) - Quintero‐Rivera, Fabiola; Woo, Jennifer S.; Bomberg, Eric M.; Wallace, W. Dean; Peredo, Jane; Dipple, Katrina M.
<x xml:space="preserve">Abstract</x> Deletions of chromosome 17q12 [OMIM 614527] encompass a wide range of phenotypes, including renal cysts, diabetes mellitus, pancreatic structural abnormalities, genital tract anomalies, developmental delay, learning difficulties, and more recently, autism spectrum disorder and schizophrenia. To date, gastrointestinal malformations have not been fully characterized in this syndrome. In this case report, we describe a four‐year‐old girl with a 17q12 microdeletion who was born with duodenal atresia, bilateral renal cysts, left kidney dysplasia, a midline cystic structure at the conus medullaris, and dysmorphic features. Both the patient and her affected father were found to have a deletion of 17q12, which encompasses the HNF1B (hepatocyte nuclear factor beta). It is hypothesized that HNF1B may play a role in intestinal differentiation and development. Our clinical report further expands the pre‐and post‐natal presentation of this rare microdeletion syndrome. © 2014 Wiley Periodicals, Inc.